1978
DOI: 10.1111/j.1476-5381.1978.tb08655.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of L‐tryptophan and Monoamine Oxidase Inhibitors on Catecholamine Metabolism in Rat Brain

Abstract: 1 L-Tryptophan (100 mg/kg) was administered to rats with or without pretreatment with a monoamine oxidase inhibitor and the concentration of 5-hydroxyindoleacetic acid, homovanillic acid, dihydroxyphenylacetic acid, 3-methoxy 4-hydroxyphenyl glycol, normetanephrine, noradrenaline and dopamine measured in whole brain one hour later. 2 L-Tryptophan increased the concentration of 5-hydroxyindoleacetic acid, homovanillic acid, dihydroxyphenylacetic acid, 3-methoxy 4-hydroxyphenyl glycol and normetanephrine. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 18 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Suppression of ejaculation was also associated with increase in the dopamine content of the lower lumbar segments. This might be explained as a consequence of dopamine release caused by the increase in serotonin, as reported by Eccleston and Nicolaou (1978). It is recognized that spinal contents of noradrenaline and serotonin are varied with different animal species.…”
Section: Discussionmentioning
confidence: 80%
“…Suppression of ejaculation was also associated with increase in the dopamine content of the lower lumbar segments. This might be explained as a consequence of dopamine release caused by the increase in serotonin, as reported by Eccleston and Nicolaou (1978). It is recognized that spinal contents of noradrenaline and serotonin are varied with different animal species.…”
Section: Discussionmentioning
confidence: 80%
“…It has been suggested that the increase in brain 5-hydroxytryptamine (5-HT) which this treatment causes in animals (Ashcroft, Eccleston & Crawford, 1965) might be the therapeutic agent. In a recent paper, Eccleston & Nicolaou (1978) showed that although 5-HT levels do rise after such treatment, the rise is associated with an increase of concentrations of CA metabolites, suggesting that the release of CA is another possible therapeutic effect. Such a mechanism was actually proposed by one of the earliest clinical investigations of the efficacy of combined tryptophan and MAOI (Pare.…”
Section: Introductionmentioning
confidence: 99%